From the Fair Theatre to the Modern Circus - Bolognesi, Mario Fernando (Revista Brasileira de Estudos da Presença, 2020)
The expulsion of the Italian comedians in 1697, and their meeting with the acrobats of the fairs of Paris, boosted the experimental effervescence of the forain scene. Stage body and performance procedures were associated with the varieties. The equestrian exercises, brought to Paris by Philip Astley, complemented the scenic matrix of the future circus show: the montage of attractions. The professionalization of artists and the formation of companies were also crucial for the commercial organization of the fairs and the modern circus.